N-type high-performance multicrystalline and mono-like silicon wafers with lifetimes above 2 ms. (5th July 2017) - Phang, Sieu Pheng; Sio, Hang Cheong; Yang, Chia-Fu; Lan, Chung-Wen; Yang, Yu-Min; Yu, Andy Wen-Huai; Hsu, Bruce Sung-Lin; Hsu, Chuck Wen-Ching; Macdonald, Daniel
Abstract: Combined with advanced crystal growth technology and reduced dislocation densities, the higher tolerance to metal contamination of n-type silicon makes n-type cast-grown silicon a potential option for low cost high quality substrates for solar cells. Using a combination of photoconductance based lifetime testing and photoluminescence imaging, we have investigated the carrier lifetime in wafers from the bottom, middle, and top parts of a n-type high-performance multicrystalline (HPM) silicon ingot, and wafers from n-type mono-like silicon ingots after each high temperature solar cell processes, including after boron diffusion, phosphorus diffusion, and hydrogenation. Although boron diffusion leads to a degradation of the sample lifetime, phosphorus diffusion and hydrogenation is effective at recovering the lifetime in the intra-grain region and at the grain boundaries respectively. Quasi-steady-state photoconductance (QSSPC) measurements show that the arithmetic average lifetime of HPM silicon wafers and mono-like silicon wafers can reach up to 1.8 and 3.3 ms respectively for a process sequence including a boron diffusion, with corresponding implied open circuit voltage of about 720 mV. If the boron diffusion can be avoided, average lifetimes up to 3.0 and 6.6 ms can be achieved respectively, highlighting the excellent potential of n-type cast-grown materials.